Examining New Urbanism Principles in Cold and Semi-Arid Climate Regions (Kayseri, Keçi Köy Neighborhood Example) (Architecture Image Studies, 2025)
In the design of historical cities, particularly in the structure of traditional neighborhoods, climate, along with the culture, identity, and sense of belonging of the neighborhood residents, holds great importance. The patterns and structural models of old settlements have been constructed over thousands of years through collective human experiences. Following the Industrial Revolution and the widespread use of automobiles, significant issues arose in urban and neighborhood design, leading to various problems alongside changes in neighborhood fabric. To address the challenges of this era, contemporary urbanism approaches (such as New Urbanism, Eco-City, Smart Growth, Sustainable Urbanism, Compact City, Neighborhood Unit, and other approaches) have been proposed. The hypothesis of this research suggests that many of these contemporary urbanism approaches already exist in Turkey’s traditional urban textures, indicating that these approaches are not entirely new. This study focuses on the evaluation of New Urbanism principles in the historical neighborhood of Kiçiköy in Kayseri, a great example of a traditional Turkish neighborhood located in a cold and semi-arid climate. This neighborhood was selected due to its preserved traditional structure and its protection by local municipalities. The research was conducted using field research methods, complemented by theoretical insights gathered from books, articles, and theses. The ten principles of New Urbanism were analyzed in the Kiçiköy neighborhood using maps, visuals, and evaluations. Subsequently, this information was assessed using a Likert scale (a five-point scale ranging from very poor to very good). Based on the Likert scale results, it was observed that the urban fabric of Kiçiköy is in full alignment with the principles of New Urbanism. These findings indicate that modern urbanism approaches, such as New Urbanism, are not entirely new concepts but have long existed within the structure of traditional Turkish neighborhoods.